A Discrete Event Simulation Based Approach for Digital Twin Implementation. Issue 1 (2021) - Morabito, Lucrezia; Ippolito, Massimo; Pastore, Erica; Alfieri, Arianna; Montagna, Francesca
Abstract: Nowadays, manufacturing companies need to improve their production monitoring and prediction to be more flexible and re-configurable. To do so, the digitization of the manufacturing environment is a very critical issue. This paper proposes an approach to develop digital twins in this environment. Digital twins are virtual systems, real time connected with their physical counterpart, which replicate exactly their behaviour. Discrete event simulation models, connected in real-time with their real system counterparts, are developed in this work. Two industrial use cases are analysed, to show the benefits that this promising technology can bring to the manufacturing industry.